Using Lego Mindstorms Robotics Programming in Enhancing Computational Thinking among Middle School in Saudi Arabia - Ahmad Alalawi, Wafa; Nihra Haruzuan Bin Mohamad Said, Mohd. (International Journal of Psychosocial Rehabilitation, 2020)
The study employed will employ LEGO Mindstorms EV3 robotics in the learning environment of the computer curriculum of the 3rd level of Saudi Arabia middle schools to examine whether this kind of learning environment enhances computational thinking skills and learning programming concepts and attitudes toward learning. The study will be conducted in Riyadh. 60 student participants will be selected through purposive sampling techniques to participate in a quasi-experimental study. Before the implementation of the experimental study, a preliminary study will be conducted through a descriptive survey among students who are randomly selected from middle schools in Saudi Arabia to respond to computational thinking tests and attitude questionnaires to determine their level of CT and their attitude toward learning programming. After that, the researcher will do the experimental study with both groups. The T-test will be conducted to compare both groups’ scores for CT and test for programming skills from their books and questionnaires for students’ attitude toward learning to program with LEGO Mindstorms Ev3. However, the results of the pre-test and post-test will help to reveal the differences between both groups in this study. Furthermore, the result will help to build a framework for implementing CT with LEGO Mindstorms robotics in learning programming in the computer curriculum of Saudi Arabia middle schools.